THE CORRELATION BETWEEN THE USE OF BATTERY PERCUSSION INSTRUMENTS WITH THE LOW BACK PAIN MYOGENIC COMPLAINT OF THE PERCUSSION DIVISION PLAYERS OF THE MARCHING BANDS IN DENPASAR AND BADUNG - Putu Intan Noviyanti; Ni Luh Nopi Andayani; M. Widnyana; Luh Made Indah Sri Handari Adiputra (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2020)
Background: Low back pain (LBP) is a kind of complaint which is easily found in human’s daily life. An activity of carrying something can be one of factors causing the low back pain. Many people uphold some things more than the normal limit by using a wrong way and even doing it for a long duration. A battery percussion player is required to uphold and sustain a battery percussion instrument with an upright standing position and for quite a long time. It can cause the low back pain. Purpose: to find out the correlation between the use of battery percussion instruments with the low back pain myogenic complaint of the percussion division players. Method: This study used an observational analytic method with cross sectional approach which applied a saturation sampling technique. The number of the sample was 90 people divided into 3 groups: snare drum, quint tom/ multi toms and bass drum in which each group contained of 30 people. The data collection was conducted by filling out a questionnaire to diagnose and measure the pain scale with VAS. The hypothesis test was done using bivariate analysis with a chi-square test. Result: The result of the study shows that the bivariate analysis with the chi-square test finds out that the value is p < 0.05. Furthermore, the low back pain percentage of the snare drum is 63.4%; the quint tom/multi toms is 100%; and, the bass drum is 90.1%. Conclusion: Based on the result of the study, it can be concluded that there is a correlation between the use of battery percussion instruments and the low back pain myogenic complaint of the percussion division players of the marching bands in Denpasar and Badung. Key Words: Low Back Pain, Marching Band, Battery Percussion, VAS.